A Novel Differential-based Protection Scheme for Intertie Zone of Large-Scale Centralized DFIG Wind Farms - Rezaei N.; Uddin M.N.; Amin I.K.; Othman M.L.; Marsadek M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Asynchronous generators; Electric equipment protection; Electric fault currents; Electric power system interconnection; Electric power transmission networks; Electric utilities; Relay protection; Wind power; Differential relay; Distance relay; Intertie system; Overcurrent relays; Power system protection; Wind farm; Electric power system protection